Ensaios econômicos sobre fecundidade - Pereira, Juliana Patrícia Alves (2021)
The reduction in the fertility rate below the population replacement level generates a reduction in the population volume and its aging, raising the need to analyze which factors may be associated with the drop in the fertility rate over the years. Thus, this thesis comprises two essays on an economic approach to fertility. The rst essay aims to analyze the changes in the fertility rate in Brazil by observing this process along the intensive (number of children) and extensive (probability of rst child) margins. The parameters of the intensive fertility margin were rst estimated by Linear Regression, using the Ordinary Least Squares Model (OEM), and then the Poisson and Negative Binomial regression models were used, enabling a comparison of the parameters estimated by the two models and giving greater robustness to the results. Poisson and Negative Binomial models are frequently used to estimate count data in which random variables take on integer and non-negative values, as is the case of the dependent variable considered here (number of children per woman). Regarding the extensive margin, its parameters were estimated using the Probit Model. The database includes the Demographic Censuses for the years 1991, 2000 and 2010. The results show evidence of an increase in the fertility rate in the intensive and extensive margins when there is na improvement in investment conditions in the quality of children. The second essay aims to study the e ects of international trade on the fertility rate, this analysis being a still incipient literature that has gained more empirical evidence in recent years. The information was extracted from the World Development Indicators (WDI), of the World Bank, covering the period between 1990 and 2018. A panel with 162 countries was used, separated according to the annual per capita income of the population, and the estimations were performed in two stages. The rst stage measures the ow of international trade through the gravitational model, according to Anderson et al. (2015). The second analyzes the impact of international trade on the fertility rate. The estimates showed statistical relevance, especially with the application of the Gravitational Model, through its instruments based on geographic indicators.